A Bis(pyridine N‐oxide) Analogue of DOTA: Relaxometric Properties of the GdIII Complex and Efficient Sensitization of Visible and NIR‐Emitting Lanthanide(III) Cations Including PrIII and HoIII1. Issue 45 (18th September 2014) - Martins, André F.; Eliseeva, Svetlana V.; Carvalho, Henrique F.; Teixeira, João M. C.; Paula, Carlos T. B.; Hermann, Petr; Platas‐Iglesias, Carlos; Petoud, Stephane; Tóth, Éva; Geraldes, Carlos F. G. C.
Abstract We report the synthesis of a cyclen‐based ligand (4, 10‐bis[(1‐oxidopyridin‐2‐yl)methyl]‐1, 4, 7, 10‐tetraazacyclododecane‐1, 7‐diacetic acid=L1) containing two acetate and two 2‐methylpyridine N‐oxide arms anchored on the nitrogen atoms of the cyclen platform, which has been designed for stable complexation of lanthanide(III) ions in aqueous solution. Relaxometric studies suggest that the thermodynamic stability and kinetic inertness of the GdIII complex may be sufficient for biological applications. A detailed structural study of the complexes by 1H NMR spectroscopy and DFT calculations indicates that they adopt an anti‐Δ(λλλλ) conformation in aqueous solution, that is, an anti‐square antiprismatic (anti‐SAP) isomeric form, as demonstrated by analysis of the 1H NMR paramagnetic shifts induced by YbIII. The water‐exchange rate of the GdIII complex is <alternatives> <![CDATA[k298ex]]> <inline-graphic xlink:href="ark:/27927/pgh2chp85b9" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>=6.7×106 s−1, about a quarter of that for the mono‐oxidopyridine analogue, but still about 50 % higher than the <alternatives> <![CDATA[k298ex]]> <inline-graphic xlink:href="ark:/27927/pgh2chp85cv" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> of GdDOTA (DOTA=1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7, 10‐tetraacetic acid). The 2‐methylpyridine N‐oxide chromophores can be used to sensitize a wide range of LnIII ions emitting in both the visible (EuIII and TbIII) and NIR (PrIII, NdIII, HoIII, YbIII) spectral regions. The emission quantum yield determined for the YbIII complex (<alternatives> <![CDATA[QLYb]]> <inline-graphic xlink:href="ark:/27927/pgh2chp86bt" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>=7.3(1)×10−3) is among the highest ever reported for complexes of this metal ion in aqueous solution. The sensitization ability of the ligand, together with the spectroscopic and relaxometric properties of its complexes, constitute a useful step forward on the way to efficient dual probes for optical imaging (OI) and MRI.